Anaerobic digestion co-substrate of dairy cow manure and tofu cake: focusing on mixing organic ratio - Sutaryo, Sutaryo; Adiwinarti, Retno; Sahrudi, Dian; Huda, Muhammad Misbahul; Himawan, Farhan Hendri; Ward, Alastair James (Journal of Environmental Engineering and Landscape Management, 2022)
Anaerobic digestion of dairy cow manure (DCM) is constrained by a low methane production of animal manure. A method to overcome that is by co-digestion DCM and food industry by-product. This study investigated the process performance anaerobic co-digestion of DCM and tofu cake (TC) at different volatile solid (VS) mixing ratios. The treatments were partial substitutions of DCM with TC by 5%, 10%, and 15% (w/w) in reactors T2, T3, and T4 respectively, while T1 was served as control. Co-substrate of DCM and TC gave a positive effect (P < 0.05) on methane production by 24.23, 34.74, and 52.51% respectively for T2, T3, and T4 compared to the control reactor. Low total volatile fatty acids, ammonia nitrogen concentration, stable methane production and neutral pH values of all digested slurries indicate that TC is suitable to increase methane production of DCM up to a DCM/TC ratio of 2.92:1, in terms of VS.